Political cultures and resilience in education - Soto Arango, Diana Elvira; Universidad Pedagógica y Tecnológica de Colombia; Rátiva Velandia, Marlén; Mora García, José Pascual; Bernal Villate, Sandra Liliana; Universidad Pedagógica y Tecnológica de Colombia; Gómez Velazco, Nubia Yaneth; Universidad Pedagógica y Tecnológica de Colombia; Semanate Navia, Carmen Elvira; Universidad Pedagógica y Tecnológica de Colombia; Báez Osorio, Miryam; Universidad Pedagógica y Tecnológica de Colombia; Parra Báez, Lina Adriana; Universidad Pedagógica y Tecnológica de Colombia; Paternina Soto, Liliana; Universidad Pedagógica y Tecnológica de Colombia; Pulido, Diana Carolina; Universidad Pedagógica y Tecnológica de Colombia (UPTC Editorial, 2022)
The central themes of the book are resilient pedagogy, sustainable peace, Higher Normal Schools, and philosophy for everyday life, which are approached from three categories of analysis such as: self-knowledge, the imaginary of political culture in today’s teachers, and social transformation. The latter contributes to the proposal of teacher education in the 21st century as agents of change capable of intervening in education public policies from their relationship with society. In addition to their role as active interlocutors in social dialogue, in search of new approaches and solutions. The book begins with a chapter on teacher education at the National Normal School between 1900 and 1930. The second chapter examines the role of resilient pedagogy in the construction of peace. The third chapter analyzes the concept of philosophy from the point of view of teachers and students.  The fourth presents the work carried out by the congregation Hermanas de la Caridad Dominicas de la  Presentación in the ENS of Soatá between 2010 and 2017. The fifth chapter addresses institutional self-evaluation as an opportunity for improvement in the face of the quality conditions established by the Ministry of National Education from a perspective of reflection, opportunity for improvement, guarantees for educational quality and ethical commitment. The book ends with a bibliographical selection of political culture and resilient pedagogy.